An assessment of non-verbal communication skills of business school campus recruits in India: implications for stakeholder communication. (2016) - Verma, Deepak; Pande, Neerja
In the present corporate world where there is an escalated focus on sustainability programs and the emergent responsibility of organisations to fulfil triple bottom line, effective communication has come to play an even more strategic role. During various communication exercises, both internal and external, with a variety of stakeholders, executives have to be skilled enough to persuasively communicate the sustainability initiatives of organisation for not only building trust and gaining acceptance but also for enhancing the credibility and image of the organisation. Research has established that non-verbal communication is as significant as verbal communication in any change initiative. As the proficiency in non-verbal communication is realised by all, business schools have the added responsibility of developing skilled management graduates ready to shoulder the responsibility of strategic communicators of change. This paper aims to assess the non-verbal communication skills of business school graduates according to the expectations of the corporate.